Taqlid from the Perspective of Religious Education - Rusnita (International Journal Education and Computer Studies (IJECS), 2022)
Islam is not just for a particular group, but for all mankind, regardless of rank or position. However, it is clear that Muslims do not have the same intelligence and ability to comprehend the laws derived from the Quran and the Sunnah, nor do they have different educational backgrounds. Therefore, those who do not have the expertise, requirements and ability to perform ijtihat have no choice but to practice Taqlid or follow mujtahid imam which is believed to be true. A person unfamiliar with the understanding of the Quran and Sunnah cannot be compelled to research the laws and regulations of Islam directly from these two sources. Taqlid is not bad for them and can even save them from mistakes and misunderstandings in the implementation and practice of Islam his Shariah. Mujtahid Imams Taqlid does not mean leaving the Quran and Sunnah. But these are precisely the Taqlid who carry out and follow the Qur'an and Sunnah as closely as possible for those who do not know how to dig up the Dharma from these two sources. Religious education in the field of fik is inseparable from following the madahabs and fatwas of the Mujtahid clerics. Both in worship, muamalah, ahwalus syahsiah, muamalat. Maliyat and Jinayat, judicial and international law fields. In this way, Islamic education in Indonesia is generally dominated by Shafi sect thought.